Pengaruh Realisasi Pajak Kendaraan Bermotor, Bea Balik Nama Kendaraan Bermotor, Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Kota Bandar Lampung Tahun 2020-2023 - Adinda Febrilia; Yulistina Yulistina; Yudhinanto CN (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to determine the effect of the Realization of Motor Vehicle Tax (PKB), Motor Vehicle Name Return Duty (BBNKB), and Regional Levy on Regional Original Revenue (PAD) of Bandar Lampung City. The independent variable contains PKB, BBNKB, and Regional Levy while the bound variable is PAD. This study uses a Quantitative Method by processing data. The sample in this study is the number of PKB, BBNKB and Regional Levy receipts from 2020 - 2023 (monthly data) as many as 48 samples. The analysis in this study is multiple linear regression analysis, classical assumption test, and hypothesis test with a significance level of 5%. From the results of the research that has been carried out, it shows that PKB, BBNKB and Regional Levy together (Simultaneous) have a significant effect of 86.4% while the remaining 23.6% are affected by other variables outside this study.